Evidence for B Cell Exhaustion in Chronic Graft-versus-Host Disease - Khoder, Ahmad; Alsuliman, Abdullah; Basar, Rafet; Sobieski, Catherine; Kondo, Kayo; Alousi, Amin Majid; Szydlo, Richard; Muftuoglu, Muharrem; Shaim, Hila; Apperley, Jane F.; Gokdemir, Elif; Cooper, Nichola; et al. (Frontiers in Immunology, 2018)
Chronic graft-versus-host disease (cGvHD) remains a major complication of allogeneic hematopoietic stem cell transplantation (HSCT). A number of studies support a role for B cells in the pathogenesis of cGvHD. In this study we report the presence of an expanded population of CD19+CD21- B cells with features of exhaustion in the peripheral blood of patients with cGvHD. CD21- B cells were significantly increased in patients with active cGvHD compared to patients without cGvHD and healthy controls (HC) (median 12.2% vs. 2.12% vs. 3%, respectively; p<0.01). Compared with naïve (CD27-CD21+) and classical memory (CD27+CD21+) B cells, CD19+CD21- B cells in cGvHD were CD10 negative, CD27 negative and CD20hi, and exhibited features of exhaustion, including increased expression of multiple inhibitory receptors such as FCRL4, CD22, CD85J and altered expression of chemokine and adhesion molecules such as CD11c, CXCR3, CCR7 and CD62L. Moreover, CD21- B cells in cGvHD patients were functionally exhausted and displayed poor proliferative response and calcium mobilization in response to B-cell receptor triggering and CD40 ligation. Finally, the frequencies of circulating CD21- B cells correlated with cGvHD severity in patients after HSCT. Our study further characterizes B cells in chronic cGVHD and supports the use of CD21- CD27- CD10 - B cell frequencies as a biomarker of disease severity.